2014
DOI: 10.1016/j.jenvp.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Charges for plastic bags: Motivational and behavioral effects

Abstract: (2014This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T A C C E P T E D ACCEPTED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 28 publications
5
76
0
2
Order By: Relevance
“…As recognized in the review work by Klöckner (2013), understanding change in an individual's habits (behaviors that have become automatized through repetition), is also amongst the best direct predictors of behavior change ( Table 1). Examples of methods that could be applied, include observing individual's behavior in supermarkets in relation to purchasing choice, as applied for plastic bag use by Jakovcevic et al (2014), or frequency of undertaking a behavior such as littering in parks (Schultz et al, 2013). For participants of an ocean literacy initiative with an associated app or social media site, frequency of visits to the social media site or of accessing information resources on an app within smart phones can be undertaken (Ernsting et al, 2017;Dempsey et al, 2018).…”
Section: Improving Experimental Approachesmentioning
confidence: 99%
“…As recognized in the review work by Klöckner (2013), understanding change in an individual's habits (behaviors that have become automatized through repetition), is also amongst the best direct predictors of behavior change ( Table 1). Examples of methods that could be applied, include observing individual's behavior in supermarkets in relation to purchasing choice, as applied for plastic bag use by Jakovcevic et al (2014), or frequency of undertaking a behavior such as littering in parks (Schultz et al, 2013). For participants of an ocean literacy initiative with an associated app or social media site, frequency of visits to the social media site or of accessing information resources on an app within smart phones can be undertaken (Ernsting et al, 2017;Dempsey et al, 2018).…”
Section: Improving Experimental Approachesmentioning
confidence: 99%
“…Sampling and observation protocols need to be carefully designed and recorded and inter-observer reliability should be established to ensure data quality 23 . For example, Jacovcevich et al 24 observed consumer behaviour in several Argentinian supermarkets before and after plastic bag charges were introduced. As expected, consumer use of reusable bags increased and kept increasing for several months after the charge was introduced.…”
Section: Measuring People's Perceptions and Behaviours: Quantitative mentioning
confidence: 99%
“…Studies which measure self-reported behaviour using questionnaires may be affected by bias (Van de Mortel et al, 2008) or poor memory (Jakovcevic et al, 2014), and may not truly represent behaviour occurring in the real world (Kormos & Gifford, 2014). Kormos and Gifford (2014) found that in the association between self-reported pro-environmental behaviour and objective behavioural measurements, the majority of the variance was unexplained.…”
Section: )mentioning
confidence: 99%
“…Despite testing all available variables, we made predictions on the expected predictors of frequent plastic bag purchasing based on two different components 1) the characteristics of people who intend to not consume plastic bags (Jakovcevic et al, 2014;Poortinga et al, 2016); and 2) the characteristics influencing people's ability to convert intentions to behaviour (Bamberg & Möser, 2007;Hines et al, 1987).…”
Section: Predictionsmentioning
confidence: 99%